Computational Pressure-Fluid Dynamics Applied to Index of Microcirculatory Resistance, Predicting the Prognosis of Drug-Coated Balloons Compared With Drug-Eluting Stents in STEMI Patients - Duan, Yang; Wang, Yiwen; Zhang, Min; Li, Zhi; Chen, Lei; Miao, Hao; Pei, Siyu; Lu, Yuan; Wang, Zhirong (Frontiers in Physiology, 2022)
Background The impairment of microvascular injury on prognosis has increasingly drawn extensive awareness along with the high morbidity and mortality of STEMI over recent years. The prognostic significance of CPFD-caIMR in microvascular injury evaluation of STEMI patients remained inconclusive. Methods A total of 213 patients who met the inclusion criteria were selected retrospectively from 1003 STEMI patients from February 2018 to February 2020. PSM was thereafter finished. CPFD-caIMR of all patients was obtained off-line using the software (FlashAngio, Rainmed Ltd., Suzhou, China) after PPCI. The primary endpoint was to compare the CPFD-caIMR and the incidence of MACEs between DCB and DES groups. The correlation between CPFD-caIMR and MACEs was analyzed, and the prognosis of patients with STEMI was evaluated by CPFD-caIMR by multivariate regression analysis. Results Totally 213 STEMI patients with successful PPCI were included, of whom 84 patients accepted DCB and 129 patients accepted DES respectively. Baseline characteristics and CPFD-caIMR were comparable between DCB and DES groups after PSM (62 patients in each group). CPFD-caIMR was not significantly different between two groups (DES vs DCB: mean difference: 2.26, 95% CI -4.05 to 8.57, P = 0.45), and so was it when re-grouped by whether CPFD-caIMR > 40U or not (DES vs DCB: 34.17% vs 27.16%, P = 0.29). After a follow-up of 1 year, more MACEs occurred in DES group than DCB group (relative risk: 2.50, 95% CI 1.04 to 6.02, P = 0.04). The predictors of MACEs by multi-variate analysis found that, only time from symptom to balloon (P = 0.03) and time from door to balloon (P < 0.01) were independent predictors of MACEs, independent of treatment with DCB or DES intervention. Furthermore, CPFD-caIMR > 40U became an independent predictor of the combined events including cardiovascular deaths or heart failure readmission irrespective of PSM (odds ratio: 4.07, 95% CI: 1.058 to 7.66, P = 0.04). Conclusions CPFD-caIMR was a promising method for prognosis, which can predict CV death or heart failure readmission in STEMI patients. DCB was a possible strategy in PPCI of STEMI patients, not inferior to DES based on microvascular injury evaluated by CPFD-caIMR.